Dados astron?micos: uma proposta de implementa??o para banco de dados - Santana, Edcarlos da Silva (2018)
With the advent of computing, the way of doing science has changed circumstantially, revolutionizing scientific research. In astronomy, telescopes now equipped with increasingly modern sensors, produce data quantities never seen before, making it impossible to exhaust all the capacity to extract knowledge from the data produced, thus presenting conditions of reuse by their peers or other purposes. The value of this data to Science lies in its unexplored potential. In this sense, this work shares the philosophy of Virtual Observatories, regarding the reuse of old data. Therefore, this dissertation is about the implementation of procedures and computational techniques that allow to organize and search for images from telescopes. Images that were found were of the exclusive period. With this, studies were developed on data structure, computational tools, algorithms and programming languages that could contribute to the development and resolution of the research problem under analysis.